2020
DOI: 10.1590/0074-02760200080
|View full text |Cite
|
Sign up to set email alerts
|

Increased platelet distribution width and reduced IL-2 and IL-12 are associated with thrombocytopenia in Plasmodium vivax malaria

Abstract: BACKGROUND Thrombocytopenia in malaria involves platelet destruction and consumption; however, the cellular response underlying this phenomenon has still not been elucidated. OBJECTIVE To find associations between platelet indices and unbalanced Th1/Th2/Th17 cytokines as a response to thrombocytopenia in Plasmodium vivax infected (Pv-MAL) patients. METHODS Platelet counts and quantification of Th1/Th2/Th17 cytokine levels were compared in 77 patients with uncomplicated P. vivax malaria and 37 healthy donors fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Finally, 20 studies [ 28 47 ] were included for qualitative and quantitative syntheses. These studies included 12 [ 28 36 , 44 , 46 , 47 ] that compared IL-1β levels in severe and uncomplicated malaria and 8 [ 37 43 , 45 ] that compared IL-1β levels in patients with uncomplicated malaria and healthy controls (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, 20 studies [ 28 47 ] were included for qualitative and quantitative syntheses. These studies included 12 [ 28 36 , 44 , 46 , 47 ] that compared IL-1β levels in severe and uncomplicated malaria and 8 [ 37 43 , 45 ] that compared IL-1β levels in patients with uncomplicated malaria and healthy controls (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Briefly, the included studies were published between 1994 and 2020. The included studies were case–control studies (8/20, 40%) [ 29 , 33 , 36 , 37 , 40 , 43 , 44 , 46 ], cross-sectional studies (6/20, 30%) [ 30 , 31 , 34 , 39 , 41 , 45 ], prospective observational studies (5/20, 25%) [ 28 , 35 , 38 , 42 , 47 ] and a cohort study [ 32 ]. The included studies were conducted in Africa (10/20, 50%) [ 28 , 30 , 31 , 33 , 34 , 36 , 38 , 43 , 44 , 47 ], South America (4/20, 20%) [ 37 , 40 , 41 , 45 ], Asia and Oceania [ 29 , 35 , 46 ], Europe [ 39 , 42 ] and North America [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The overexpression of TIM3 was associated with a decreased risk of clinical malaria [71]. In a group of patients infected with P. vivax, Costa et al have found thrombocythemia and low levels of IL-2 and IL-12 that correlated with platelet distribution width (PDW) values and concluded that these changes may represent an immune response to thrombocytopenia [72].…”
Section: Has An Anti-inflammatory Effect By Inhibiting Th1 Cell Differentiationmentioning
confidence: 99%
“…Elevated IL-12 levels were suggested to play an essential role against systemic damage induced by malaria parasites [ 27 ]. Decreased IL-12 levels were related to thrombocytopenia in P. vivax malaria [ 28 ]. A previous study showed no difference in IL-12 levels between patients with malaria and non-malaria [ 29 ].…”
Section: Introductionmentioning
confidence: 99%